Determining the relationship between the speed of motion of large permanent magnets and the trajectory of implants in magnetic stereotaxic systems - Ц. Ханькунь; О. Г. Аврунін (Біофізичний вісник)
Background: The magnetic stereotaxic system is a new type of neurosurgical intervention that is in the experimental stage. This method allows the implant to be controlled non-contact by an external magnetic field, allowing it to move along an arbitrary trajectory to a lesion located in a deep structure of the brain tissue to deliver hyperthermia to the lesion site or deliver medication through a catheter. In previous studies, we have found that it is completely feasible for the implant to move along the arc trajectory, so we need to determine the relationship between the movement speed of the large permanent magnet that constitutes the external magnetic field and the implant movement trajectory, so as to control the implant movement more precisely.